Methodological Notes on Classroom (Action) Research: Rethinking the Role of Inferential Statistics and Individual Learning Evidence - Piromsombat, Chayut (Journal of Research Methodology, 2025)
This article offers methodological reflections based on the author’s experience reviewing classroom action research and educational theses. It points out common issues such as misuse of statistical tests, failure to question underlying research assumptions, and the neglect of individual-level data. The author proposes alternative approaches including the use of normalized gain scores, individual line graph analysis, and qualitative data collection and interpretation. These methods aim to capture meaningful change beyond simply reporting p-values. The article invites teachers, graduate students, researchers, and other stakeholders to reconsider prevailing research practices and adopt more appropriate, context-sensitive methods.